Α1 adrenoceptor activation by norepinephrine inhibits LPS‐induced cardiomyocyte TNF‐α production via modulating ERK1/2 and NF‐κB pathway. Issue 2 (5th December 2013) - Yu, Xiaohui; Jia, Baoyin; Wang, Faqiang; Lv, Xiuxiu; Peng, Xuemei; Wang, Yiyang; Li, Hongmei; Wang, Yanping; Lu, Daxiang; Wang, Huadong
Abstract Cardiomyocyte tumour necrosis factor α (TNF‐α) production contributes to myocardial depression during sepsis. This study was designed to observe the effect of norepinephrine (NE) on lipopolysaccharide (LPS)‐induced cardiomyocyte TNF‐α expression and to further investigate the underlying mechanisms in neonatal rat cardiomyocytes and endotoxaemic mice. In cultured neonatal rat cardiomyocytes, NE inhibited LPS‐induced TNF‐α production in a dose‐dependent manner. α1‐ adrenoceptor (AR) antagonist (prazosin), but neither β1‐ nor β2‐AR antagonist, abrogated the inhibitory effect of NE on LPS‐stimulated TNF‐α production. Furthermore, phenylephrine (PE), an α1‐AR agonist, also suppressed LPS‐induced TNF‐α production. NE inhibited p38 phosphorylation and NF‐κB activation, but enhanced extracellular signal‐regulated kinase 1/2 (ERK1/2) phosphorylation and c‐Fos expression in LPS‐treated cardiomyocytes, all of which were reversed by prazosin pre‐treatment. To determine whether ERK1/2 regulates c‐Fos expression, p38 phosphorylation, NF‐κB activation and TNF‐α production, cardiomyocytes were also treated with U0126, a selective ERK1/2 inhibitor. Treatment with U0126 reversed the effects of NE on c‐Fos expression, p38 mitogen‐activated protein kinase (MAPK) phosphorylation and TNF‐α production, but not NF‐κB activation in LPS‐challenged cardiomyocytes. In addition, pre‐treatment with SB202190, a p38 MAPK inhibitor, partly inhibited LPS‐induced TNF‐α production in cardiomyocytes. In endotoxaemic mice, PE promoted myocardial ERK1/2 phosphorylation and c‐Fos expression, inhibited p38 phosphorylation and IκBα degradation, reduced myocardial TNF‐α production and prevented LPS‐provoked cardiac dysfunction. Altogether, these findings indicate that activation of α1‐AR by NE suppresses LPS‐induced cardiomyocyte TNF‐α expression and improves cardiac dysfunction during endotoxaemia via promoting myocardial ERK phosphorylation and suppressing NF‐κB activation.